(untitled) (Research, Society and Development, 2022)
The aim of this study was to look into the repercussions of childbirth care models on the experiences of fathers and mothers. A qualitative research investigation was carried out through a collective case study, in which 30 birth reports published on personal blogs dealing with pregnancy, childbirth and parenthood experiences were analyzed, 15 written by women and 15 by men. The results pointed to the helplessness felt by fathers and mothers in the face of technocratic assistance and to the idealization of childbirth care offered by health professionals who work according to the humanized model. The idea of ​​choosing the mode of delivery appeared frequently in the reports, pointing to a scenario in which caesarean section is understood as a consumer good. It was concluded that care, support and respect for the parturient should be promoted by health professionals as fundamental requirements for childbirth care.